2015
DOI: 10.1111/jvim.13572
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Balloon Dilation of Esophageal Strictures in 9 Horses

Abstract: BackgroundMedical treatment of esophageal strictures in horses is limited and the use of balloon dilatation is described in few cases. Long‐term follow up after balloon dilatation and the use of intralesional corticosteroids has not been evaluated.ObjectivesTo describe the use of endoscopic guided, esophageal balloon dilatation in horses for cervical and thoracic esophageal strictures and administration of intralesional corticosteroids at the time of dilatation.AnimalsNine horses from the hospital population w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 21 publications
(58 reference statements)
0
20
0
1
Order By: Relevance
“…Use of the technique in equine oesophageal strictures has been reported once, with 3 of the 4 treated horses surviving without recurrence of the stricture (Prutton et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Use of the technique in equine oesophageal strictures has been reported once, with 3 of the 4 treated horses surviving without recurrence of the stricture (Prutton et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, the presence of megaoesophagus did not appear to negatively affect long‐term outcome in Foal B , in comparison to the study by Prutton et al . (), which found that animals with concurrent megaoesophagus had a worse prognosis.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…; Prutton et al . ). Of these disorders, only a few have been reported to manifest with clinical signs in neonatal foals (Petrick et al .…”
Section: Introductionmentioning
confidence: 97%